Trustworthy intelligence, sustainable systems, and resilient digital infrastructure for an AI-driven future - Tole Sutikno (Institute of Advanced Engineering and Science, 2026)
This editorial introduces Volume 42, Number 2, May 2026 of the Indonesian Journal of Electrical Engineering and Computer Science (IJEECS), which presents a broad collection of peer-reviewed research contributions spanning electrical engineering, electronics, computer science, artificial intelligence, cybersecurity, and information and communication technologies. The issue highlights the growing convergence of intelligent systems, sustainable engineering, trusted digital infrastructures, and data-centric innovation in addressing contemporary global challenges. The published articles demonstrate advances in renewable energy technologies, intelligent control systems, AI-enabled healthcare, cybersecurity, graph-based learning, Internet of Things (IoT) architectures, smart agriculture, educational technologies, and uncertainty-aware data management. Collectively, these contributions emphasize the importance of integrating intelligence, resilience, sustainability, and ethical considerations into next-generation engineering solutions. The issue further reflects emerging research directions focused on trustworthy artificial intelligence, secure cyber-physical systems, resource-efficient computing, and human-centered digital transformation. Through interdisciplinary innovation and practical implementation, the published works contribute to advancing technological systems capable of supporting sustainable development, economic growth, and societal well-being in an increasingly connected world.